Alignment-assisted field-free orientation of rotationally cold CO molecules - Ren, Xiaoming; Makhija, Varun; Li, Hui; Kling, Matthias F.; Kumarappan, Vinod (My University, 2014)
We follow the alignment-assisted orientation technique proposed by Zhang et al. [Phys. Rev. A 83, 043410 (2011)] to experimentally demonstrate a substantial enhancement of the field-free orientation by using a combination of single- and two-color laser pulses. When a two-color orienting pulse is preceded by a single-color aligning pulse by a suitable time, the resulting orientation is thrice as large as that obtained with the two-color pulse alone. We ensure that the orientation is the result of the hyperpolarizability interaction rather than ionization depletion by keeping the ionization due to the pump pulses small and demonstrate a useful level of orientation without the complications of a partially ionized target.